2011
DOI: 10.3109/00016489.2011.616532
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of balance in migraineurs

Abstract: After 1 year migraineurs showed a slight but statistically significant deterioration: in postural sway especially, when measured with eyes closed standing on a foam surface with the head extended backwards; in reaction time; and in maximal excursion on the limits of the stability test; and perhaps in walk speed and step width on the tandem walk test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
1
28
2
5
Order By: Relevance
“…1,39 However, the effects of dizziness on the postural control of migraineurs remain controversial. 27 Akdal et al 23 found differences among migraineurs and control subjects in the FoamOE testing condition of the mSOT, while our results found no difference between the results in the control group and the migraine group without aura for this test. However, the same was not evidenced by Furman et al, 9 Panichi et al 26 nor Ongun et al 25 Our study shows a high prevalence of dizziness at the ictal period in migraineurs without aura (43%), migraineurs with aura (43%) and in subjects with chronic migraine (49%), without significant differences among the groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…1,39 However, the effects of dizziness on the postural control of migraineurs remain controversial. 27 Akdal et al 23 found differences among migraineurs and control subjects in the FoamOE testing condition of the mSOT, while our results found no difference between the results in the control group and the migraine group without aura for this test. However, the same was not evidenced by Furman et al, 9 Panichi et al 26 nor Ongun et al 25 Our study shows a high prevalence of dizziness at the ictal period in migraineurs without aura (43%), migraineurs with aura (43%) and in subjects with chronic migraine (49%), without significant differences among the groups.…”
Section: Discussioncontrasting
confidence: 67%
“…[16][17][18] The extension of the subclinical ischemic-like lesions is not correlated with the subjects' age, 19 but rather shows a positive correlation with the presence of aura, 20,21 with disease duration, and with the frequency of pain episodes. 4 Among the abnormalities, deficits at the semi-static balance control, 2,5,[9][10][11]15,[23][24][25][26] changes of stability limits, 23,27 reduced gait and tandem gait velocities are reported. 4 Among the abnormalities, deficits at the semi-static balance control, 2,5,[9][10][11]15,[23][24][25][26] changes of stability limits, 23,27 reduced gait and tandem gait velocities are reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are now official criteria for the diagnosis of VM [64, 67], even though many migraineurs have other, unofficial, balance problems, such as chronic subjective dizziness [68], motion sensitivity [69], motion sickness [70], constant rocking sensations (mal-de-debarquement) [71], room-tilt illusion [45], and generalized imbalance [72]. And, perhaps as a consequence of the vertigo attacks, VM patients have psychological problems such as anxiety [73], panic attacks [74], and phobias [75].…”
Section: Vestibular Migrainementioning
confidence: 99%
“…In general, VM is part of the broader migraine syndrome and the patient also suffers from migraine with aura. Cerebellar eye movement and impaired balance have also been described in migraine without vertigo (25,26). The role of the cerebellum in migraine warrants further study.…”
Section: Is Vestibular Migraine (Vm) Part Of This Canvasmentioning
confidence: 95%